Climate Change Dominated Long‐Term Soil Carbon Losses of Inner Mongolian Grasslands. Issue 10 (26th October 2020) - Xin, Xiaoping; Jin, Dongyan; Ge, Yong; Wang, Jianghao; Chen, Jiquan; Qi, Jiaguo; Chu, Housen; Shao, Changliang; Murray, Philip J.; Zhao, Ruixue; Qin, Qi; Tang, Huajun
Abstract: Soil organic carbon (SOC) is the most critical component of global carbon cycle in grassland ecosystems. There has been growing interest in understanding SOC dynamics and driving forces of grassland biomes at various temporal and spatial scales. Up to now, estimates of long‐term and large‐scale changes in SOC of grassland biomes have been mostly based on modeling approaches and manipulative experiments, rather than direct measurements. During 2007–2011, we repeated 141 soil profiles of the sampling in 1963–1964 (up to 1‐m depth) to quantify the long‐term changes of SOC storage in the major grassland types of Inner Mongolia in order to tease apart the relative contributions of climate change and grazing. We found that SOC decreased in all soil types, except in the eolian sandy soils, from 1963 to 2007, with an average reduction rate of 1.8 kg C m −2 (~22.9% or 0.52% year −1 ) in the grassland biome of Inner Mongolia. We quantitatively clustered the soils into four groups using principal component analysis (PCA) and detected clear spatial dependency of the changes on climate and grazing. The climate change was responsible for 15.3–34.9% of the total SOC variations, whereas grazing intensity accounted for <9.5% of the changes. Our findings indicated that climate change, rather than grazing, was the primary forcing for the changes in SOC of Inner Mongolia grasslands. We presume that other driving forces, such as changes in nongrazing‐resultant wind erosion and atmospheric nitrogen deposition, might have played a role albeit their effects need to be further examined. Key Points: SOC decreased at an average rate of 0.52% year −1 in the grassland biome of Inner Mongolia Climate change rather than grazing was the major contributor to long‐term soil carbon losses